Effects of calcination on the environmental behavior of sediments by phosphorus speciation and interface characterization. (15th March 2023) - Xia, Rui; Duan, Pingzhou; Li, Rui; Jiao, Lixin; He, Jia; Ding, Shuai; Wu, Xue
Abstract: Dredged sediments derived from eutrophicated lakes poses hardness of sludge disposal and ecological risks. The proper pretreatment and utilization of dredged sediments presented a challenge. In this study, Dianchi Lake sediments were dredged, thermally treated and utilized as particle capping material in batch experiments. The effects of calcination on phosphorus speciation and sediment-water interface environment as well as P immobility mechanism were predominantly explored. The microstructures and chemical compositions of calcined sediments were investigated, indicating the porosity and mineralization components were greatly enhanced. The fractional analysis of phosphorus revealed that the calcination process reduced the percentage of unsteady phosphorus, transforming into stable inert phosphorus fractions (Al–P, Ca–P and Res-P), respectively, thereby minimized its mobility and eutrophication risk. Interestingly, calcination temperatures of 700 °C and 800 °C resulted in smaller releasing potentials and equilibrium phosphorus concentrations, despite having lower adsorption capacities than 550 °C. Furthermore, the results of redox potential monitoring showed that the thermally treated Dianchi Lake sediments could enhance the redox potential and dissolved oxygen in the surface sediment, indicating the amelioration of interfacial environment. The practical monitoring experiments confirmed the capping depressed the DTP to 0.031 mg L −1 . The investigation of this study provided explicit evidence of Ca coupled P and aerobic Fe bound P strengthened the immobilization effects, and the development of sediment calcination demonstrates a promising strategy for alleviating the burden of endogenous pollution and improving aerobic environment, which are of great significance for lake ecological remediation. Graphical abstract: Image 1 Highlights: The composition and morphology of thermally treated sediments were characterized. Phosphorus releasing potential was reduced at higher calcination temperatures. The mobile phosphorus contents were dramatically decreased by thermal treatment. SRP in overlying water can be effectively reduced by the increased Ca–P complexes.